TUTURAN RITUAL AMUNGTAPE PADA MASYARAKAT PADAILAKA DI KABUPATEN ALOR - Narantoputrayadi Makan Malay (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
This research focus on custom utterance Amungtape, brief of TRA, and in this ritual there are three utterance supporter for example; custom utterance Amung Kala Tape, custom utterance Neng Jing, and custom utterance Amung Luk of Society in Countryside of Lakatuli of Orchard Padailaka in Regency Alor . This Research is studied from in perpective of culture linguistics. its Study goals include;cover the characteristic form , meaning and assess the TRA in society life in Countryside of Lakatuli of Orchard Padailaka as main problem in this research. Seen from analyzed problem character, this research is categorized in research deskripsi. In data collecting used by some technique, that is: perception technique, interview the, directional group discussion, recording, simak-catat, and documentation study. To obtain; get the accurate data, six people selected from original penutur of Ianguage Put ash consisted of by four people selected by as informen key and its two others as informan pendamping. Data which have been collected to be analysed descriptively qualitative and also ravelled clearly from entire/all deskripsi . Key words: Tuturan Ritual Amung Kala Tape, Neng Jing, and Amung Luk, culture linguistics, form , meaning and assess.